Predicting the potential global distribution of diosgenin-contained Dioscorea species - Liang Shen; Jiang Xu; Lu Luo; Haoyu Hu; Xiangxiao Meng; Xiwen Li; Shilin Chen (BMC, 2018)
Abstract Background Diosgenin, mainly extracted from wild diosgenin-contained Dioscorea species, is a well-known starting material of steroidal and contraceptive drugs. However, due to large market demand and increasingly ecological damage, wild Dioscorea species resources available have been gradually declining. Therefore, identification of new potential ecological distribution of diosgenin-contained Dioscorea species is necessary for diosgenin production. Methods In this study, a large occurrence dataset (1808 data points) of diosgenin-contained Dioscorea species was obtained from Eastern Asia, Southern North America and Southern Africa. Along with the data for six critical environmental parameters and one soil factor, Geographic Information System for Global Medicinal Plant was applied to predict the potential suitable distribution of Dioscorea species. Results The results showed that the potential distribution of these Dioscorea species covered a wide field, and that new ecological suitability areas were mainly distributed in the central region of South America, the southern part of the European and coastal region of Oceania. Jackknife test indicated that annual precipitation and annual mean radiation were the important climatic factors controlling the distribution of Dioscorea species. Conclusions The suitable areas and critical climatic factors will serve as a useful guide for diosgenin-contained Dioscorea species conservation and cultivation in ecological suitable areas.